White blood cell Indices to predict first trimester missed miscarriage - Esraa Hameed Humadi; Hana,a Asa,ad Maki (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the relationship between white blood cell indices in missed miscarriage compared to ongoing pregnancy in the first trimester. Method: The diagnostic accuracy study was conducted at the Department of Maternity, Al-Yarmouk Hospital, Baghdad, Iraq, from January to October 2021,and comprised healthy first-trimester pregnant women in group A and those with missed miscarriage after 7-13 weeks of gestation in group B. Ultrasound findings and the last menstrual period were noted for all the subjects. Total and differential leukocyte counts, neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio were compared between the groups. Data was analysed using SPSS 22. Results: Of the 167 women, 81(48.5%) were in group A and 86(51.5%) were in group B. Demographic and obstetrics data was not significantly different between the groups (p>0.05). Mean white blood cell, neutrophil and monocyte counts showed no significant difference between the groups (p>0.05), while lymphocyte count, neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio were significantly different between the groups (p<0.05). With respect to gestational age, neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio had a fair ability to predict missed miscarriage at various time points within the first trimester (p<0.05). Conclusion: There was no significant correlation between WBC count and gestational age. Reduced MLR and NLR levels can be utilised to forecast miscarriages in a cost-effective manner. Key Words: Pregnancy, Abortion, Spontaneous, Neutrophils, Monocytes, Gestational, Lymphocytes, Miscarriage.